A study on the needs of practical training for accounting students: students' perceptions / Yusliena Yusoff - Yusoff, Yusliena (2001)
The main objective of this study is to identify the accounting students' perceptions towards the importance and the needs of a practical training program. Various job attributes previously used by Reed and Kratchman (1989) were adopted in order to meet the objectives of this study. Extensive literature on the potential benefits that can be gained from practical training had been reviewed. The other objectives of the study is to examine the perceptions of the male and female students and to determine the perceptions of BACC (Bachelor of Accountancy) students from Part 1 to Part 4 on the importance of various job attributes. The study was conducted specifically in UiTM Seksyen 17, Shah Alam by distributing questionnaires to BACC students during their class session. It was found that the students perceived very important that practical training help them build up their confidence. Other findings show that there is no significant different in perceptions between gender and among students in different parts on the importance of the various job attributes. From this study, it indicates that practical training gives may benefits to students and the students themselves perceived that the practical training is necessary and important to them. Therefore the need to include the practical attachment in the curriculum of accounting, need to be considered.